Kesiapan Guru Pendidikan Agama Islam dalam Mengintegrasikan Teknologi Pembelajaran di SMK PGRI 1 Kota Kediri - Mohammad Nanang Nurul Burhan; Zaenal Arifin; Bustanul Arifin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
In the world of education, the development of information and communication technology encourages the use of digital platforms to create more interesting, interactive and flexible learning, such as Learning Management Systems (LLMS) and video conferencing. In the context of Islamic Religious Education (PAI), challenges will arise related to ethics, culture, and teacher readiness in operating digital devices. Based on previous research reviews, there are not many studies that show the readiness of teachers, especially in the PAI subject, in integrating technology. This is important at the vocational high school level, especially at SMK PGRI 1 Kediri City which has adequate ICT facilities. The purpose of this study is to describe in depth the real conditions at SMK PGRI 1 Kediri regarding the readiness of Islamic Religious Education teachers in integrating learning technology. This study is a field research with a descriptive qualitative approach that describes and interprets data systematically according to the facts in the field. Data were collected through observation, interviews, and documentation of purposely selected informants, namely PAI teachers. The results of the study indicate that the potential for technology integration by Islamic Religious Education (PAI) teachers at SMK PGRI 1 Kota is derived from an open attitude towards technology, training, adequate facilities, and a supportive school culture, and assessing digital-based learning as more effective and efficient. The strategies used include the use of visual content such as PPT and videos, as well as formative quizzes as an engaging evaluation tool for students. This study strengthens the understanding that teacher readiness is not only determined by technical abilities alone, but also by school culture factors, institutional support, and an open attitude towards technology.